European Reform of Statutory Audit and Market Structure: The Position of Audit Firms - Loison, Marie-Claire; Belze, Loïc; Hottegindre, Géraldine (Management international / International Management / Gestiòn Internacional, 2020)
The European Commission recently reformed the statutory audit market in order to improve its competitiveness. We employ resource dependence theory to understand the position of audit firms with regard to the policy options considered. By using content analysis to examine consultation responses, we show that, despite the existing market segmentation, all sizes of firm adopt similar positions, except on the topic of audit consortia. The differences in firms’ access to resources, particularly with respect to human capital, help to explain these positions, which perpetuate supply concentration in the market.